Evaluation in humans of ELF-EMF exposure on chromogranin A, a marker of neuroendocrine tumors and stress. (2nd January 2020) - Touitou, Yvan; Lambrozo, Jacques; Mauvieux, Benoit; Riedel, Marc
ABSTRACT: Chromogranin A (CgA), which is a major protein in adrenal chromaffin cells and adrenergic neurons, is a clinically relevant endocrine and neuroendocrine tumor marker including pheochromocytomas, neuroblastomas, and related neurogenic tumors. In this study, we looked at the effect in humans of chronic daily exposure to a 50-Hz magnetic field. We examined in 15 men (38.0 ± 0.9 years) the effects of chronic daily exposure to a 50-Hz magnetic field for 1–20 yrs both at home and at work. EMDEX II dosimeters were used to record magnetic field all day long every 30 s. for 1 week. The weekly geometric mean of the individual exposures ranged from 0.1 to 2.6 μT. Blood samples were taken hourly between 20:00 h and 08:00 h. CgA patterns of exposed subjects were compared to age-matched controls. The results of exposed subjects were compared with those for 15 unexposed men who served as controls and whose individual exposure was ten times lower ranging from 0.004 to 0.092 μT. This work shows that in the control group the serum CgA levels exhibited a nighttime peak with a progressive decline of the serum concentrations and a nadir in the morning. Both the profile and the serum concentrations of CgA, a marker of neuroendocrine tumors and stress, did not appear to be impaired in the subjects chronically exposed over a long period (up to 20 yrs) to magnetic fields though a trend toward lower levels were found at the highest exposure (>0.3 μT). This does not rule out, however, that the potential deleterious risk of ELF-EMF on frail populations such as children and the elderly may be greater at low exposure and should hence be documented, at least for their residential exposure.